Translating Ethiopian potato seed networks: identifying strategic intervention points for managing bacterial wilt and other diseases - Etherton, B.A.; Sulá, A.I.P.; Mouafo-Tchinda, R.A.; Kakuhenzire, R.; Kassaye, H.A.; Asfaw, F.; Kosmakos, V.S.; McCoy, R.W.; Xing, Y.; Yao, J.; Sharma, K.; Garrett, K.A. (Cold Spring Harbor Laboratory, 2024)
Context Informal seed trade can exacerbate crop disease epidemics. Potato production across Ethiopia is threatened by the spread of seedborne pests and pathogens, particularly by bacterial wilt, caused by the Ralstonia solanacearum Species Complex (RSSC). The RSSC is commonly dispersed through informal trade of seed potato, with the potential to move long distances across Ethiopia and among trading countries. Efficient disease testing programs and formal seed systems can reduce the risk of disease expansion in a country’s potato cropping system.